2017
DOI: 10.12816/0041069
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Functional Adaptations of the Lingual Epithelium of Two Bird Species Which Have Different Feeding Habits

Abstract: The dorsal epithelium of the free portion of tongue of laughing dove, Streptopelia senegalensis (granivorous) is characterized by presence of well-developed keratinized epithelium with desquamate parakeratinized one which is covering the anterior part of the free portion. Highly keratinized and stratified epithelium is covering the ventral surface of the anterior third of the free portion of the tongue and forming the lingual nail. Laryngeal area is covered dorsally by non-keratinized squamous epithelium. Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The obtained results were parallel to those described in Muscovy duck [7], in duck [28], in pati duck [8], in domestic duck [6], in white-headed duck [30], in quails [10], in domestic pigeon [37], in mute swan [27], in Anas crecca [26], and in laughing dove [31,38] that the median lingual sulcus was detected on the dorsal aspect of the tongue in the Muscovy duck. However, Jackowiak et al [16] stated that the tongue of cormorant has a medial sacral crest in its dorsal surface.…”
Section: Discussionsupporting
confidence: 82%
“…The obtained results were parallel to those described in Muscovy duck [7], in duck [28], in pati duck [8], in domestic duck [6], in white-headed duck [30], in quails [10], in domestic pigeon [37], in mute swan [27], in Anas crecca [26], and in laughing dove [31,38] that the median lingual sulcus was detected on the dorsal aspect of the tongue in the Muscovy duck. However, Jackowiak et al [16] stated that the tongue of cormorant has a medial sacral crest in its dorsal surface.…”
Section: Discussionsupporting
confidence: 82%
“…Shawki and Ismail (2006) and Mahmoud et al (2009) mentioned the functional morphological structure of the lingual apparatus of the common moorhen and kestrel respectively and confirmed that these bird species mainly rely on their lingual apparatus in feeding process, while the hoopoe depends on the jaw apparatus in manipulating their prey than its tongue (Gadel-Rab, Shawki, & Saber, 2012) which agree with those mentioned by Rawal (1968) who concluded that the long arms of hoopoe's bill confer greater advantage in thrusting the bill into soil.…”
Section: Discussionmentioning
confidence: 96%
“…Many of the literature has studied the avian feeding system (Jackowiak & Godynicki, 2004;Mahmoud, Shawki, & Wahba, 2009;El-Bakary, 2011, 2012AlZahaby & Elsheikh, 2014;Erdogan & Iwasaki, 2014;and Shah & Aziz, 2014;Gadel-Rab, Shawki, & Saber, 2017), but still the feeding mechanics and functional morphological information about most bird species remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Histomorphological investigation for the tongue elucidated that it displayed a pattern arrangement of the lingual epithelium which was sequentially arranged in four layers including the stratum basale, stratum spinosum, stratum granulosum, and outer cornified layer, stratum corneum. The dorsal lingual epithelium was underlain by a loose connective tissue layer forming the lamina propria with the intense positive reaction for MT staining in the lingual root, together with the core of the papillary crest and laryngeal papillae (Uppal et al, 2014; Skieresz-Szewczyk & Jackowiak, 2016; Gadel-Rab et al, 2017). In our attempt to unravel the functional adaptations of the lingual microstructures, we have characterized the histological features of both salivary glands and taste buds along the lingual axis.…”
Section: Discussionmentioning
confidence: 99%